E-Finance: What Factors Affect Financial Staff's Motivation to Utilize It? - Muhammad Dimar Alam; Areta Widya Kusumadewi; Laila Fitriyah LH (Universitas Muhammadiyah Malang, 2024)
Purpose: The objective of this study is to investigate the factors that influence the intention of financial staff in the SKPDs of Malang City government to adopt e-finance. This study combines elements from the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) found in previous research. Methodology/approach: The survey method was utilized, with a sample of 155 respondents consisting of auditors employed in the financial department of Malang City's government. Data analysis was conducted using Partial Least Square (PLS) method. Findings: The study's results indicate that constructs like perceived ease of use, perceived usefulness, attitude, subjective norm, and perceived behavioral control have a positive impact on behavioral intention. Additionally, behavioral intention positively correlates with the actual behavior of financial staff using e-finance. Practical and Theoretical contribution/Originality: The study underscores the significance for e-finance providers and management to consider perceived ease of use, perceived usefulness, attitude, subjective norm, perceived behavioral control, behavioral intention, and the actual behavior of users. Research Limitation: The researcher acknowledges specific limitations inherent in this study. These constraints pertain to the dissemination of questionnaires to respondents. The researcher encountered restrictions related to regulatory boundaries that define the scope and openness of the research.